The Anti-Inflammatory Potential of Statins in Oncology: A Focus on C-Reactive Protein (CRP), Interleukin-6 (IL-6), and Tumor Necrosis Factor-Alpha (TNF-α) Modulation - Ariosta Ariosta; Banundari Rahmawati; Udin Bahrudin; Angela Kho (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Statins, widely known for their cholesterol-lowering effects, have demonstrated promising therapeutic potential in modulating chronic inflammation, a pivotal contributor to cancer progression. Elevated inflammatory biomarkers, including C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) are frequently observed cancer patients and are associated with unfavorable prognoses. This narrative review synthesizes findings from 42 recent publications (2019-2024) retrieved via PubMed, Scopus, and Web of Science, focusing on statins' impact on these biomarkers in oncologic contexts. The studies encompass both preclinical and clinical investigations examining statin type, dosage, cancer subtype, biomarker modulation, and synergy with conventional therapies. Findings indicate that lipophilic statins, such as simvastatin and atorvastatin, substantially reduce IL-6 and TNF-α levels by inhabiting the mevalonate pathway and RhoA activation, thereby downregulating transcription factors such as NF-κB. These downstream effects indirectly contribute to CRP suppression. Additionally, statins have demonstrated the capacity to enhance the efficacy of chemotherapeutic agents, particularly platinum compounds, doxorubicin, and taxanes, by sensitizing tumor cell sensitivity, reducing resistance, and promoting apoptosis. Despite these encouraging outcomes, most data derive from preclinical studies and small-scale clinical trials, often lacking standardized effect size reporting and longitudinal clinical endpoints. This review concludes that statins may serve as effective adjunctive agents in oncology through their anti-inflammatory properties. However, large-scale randomized controlled trials are essential to establish their long-term clinical utility, safety profile, and optimal application in cancer treatment Keyword: Statins, Cancer, Inflammation, IL-6, C-reactive protein